2019
DOI: 10.1111/papr.12830
|View full text |Cite
|
Sign up to set email alerts
|

Home Telemonitoring Improved Pain Registration in Patients With Cancer

Abstract: Introduction For adequate pain treatment in patients with cancer, it is important to monitor and evaluate pain regularly. Although the numeric rating scale (NRS) is implemented in hospitals in the Netherlands, pain is still not systematically registered during outpatient consultations. The aim of this study was to assess whether home telemonitoring increases pain registration in medical records of outpatients with cancer. Methods Patients with cancer were included in the intervention group (IG) when they visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…A total of 24 studies measured at least one dimension within the domain quality of care . Furthermore, 17 studies measured the dimension effectivity [ 21 , 31 , 32 , 36 - 38 , 41 , 46 - 49 , 51 - 54 , 57 , 58 ]. Most of these studies examined the effect of eHealth interventions on psychological complaints (n = 12; eg, depression, anxiety, and psychological distress).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 studies measured at least one dimension within the domain quality of care . Furthermore, 17 studies measured the dimension effectivity [ 21 , 31 , 32 , 36 - 38 , 41 , 46 - 49 , 51 - 54 , 57 , 58 ]. Most of these studies examined the effect of eHealth interventions on psychological complaints (n = 12; eg, depression, anxiety, and psychological distress).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies measured a dimension within the domain per capita costs [ 42 , 54 , 55 ]. Two studies [ 42 , 55 ] measured the dimension costs of care , and both found through economic evaluation that the intervention was likely to be equally cost-effective compared with care as usual.…”
Section: Resultsmentioning
confidence: 99%
“… 28 In another study, telemonitoring improved pain reporting and analgesic prescription among patients with cancer pain, translating to a positive effect on QoL. 29 Further essential to patients with chronic pain, continuous monitoring by nursing staff via telemedicine is associated with enhanced feelings of security and safety as well as improved patient outcomes during palliative home care. 21 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The use of modern communication tools such as telemonitoring have been found to be useful for early detection and management of moderate to severe cancer pain, and pain recall. Other benefits include improved self-management skills, less hospital visits and an increased patient satisfaction and compliance with care agreements ( Knegtmans et al , 2020 ; Oldenmenger et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%